2022
DOI: 10.3390/nano12234212
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ag-Modified α-Fe2O3/g-C3N4 Self-Assembled S-Scheme Heterojunctions with Enhanced Photothermal-Photocatalytic-Fenton Performances

Abstract: Low spectral utilization and charge carrier compounding limit the application of photocatalysis in energy conversion and environmental purification, and the rational construction of heterojunction is a promising strategy to break this bottleneck. Herein, we prepared surface-engineered plasma Ag-modified α-Fe2O3/g-C3N4 S-Scheme heterojunction photothermal catalysts by electrostatic self-assembly and light deposition strategy. The local surface plasmon resonance effect induced by Ag nanoparticles broadens the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…When the composite photocatalyst is excited by light, the photogenerated electrons of α-Fe 2 O 3 move to carbon nitride under the action of the interfacial electric field. At this time, g-C 3 N 4 loses electrons and α-Fe 2 O 3 gets electrons, so the binding energy of N and Fe shift positively and negatively, respectively [ 83 ]. Therefore, ISIXPS can characterize the direction of electron transfer in S-scheme heterojunctions.…”
Section: Preparation Of Carbon Nitride-based S-scheme Photocatalystmentioning
confidence: 99%
“…When the composite photocatalyst is excited by light, the photogenerated electrons of α-Fe 2 O 3 move to carbon nitride under the action of the interfacial electric field. At this time, g-C 3 N 4 loses electrons and α-Fe 2 O 3 gets electrons, so the binding energy of N and Fe shift positively and negatively, respectively [ 83 ]. Therefore, ISIXPS can characterize the direction of electron transfer in S-scheme heterojunctions.…”
Section: Preparation Of Carbon Nitride-based S-scheme Photocatalystmentioning
confidence: 99%
“…Currently, an effective solution is to introduce a third component, which can be categorized into two main types based on the role of the third component. In the first category, the introduced third component often consists of zero-bandgap materials, such as graphene, 7 elemental metals like Ag 8,9 and Bi, 10 carbon quantum dots, 11 Ti 3 C 2 MXene, 12 etc. These materials are uniformly dispersed within the binary components and primarily serve as conductors to enhance charge carrier transport.…”
Section: Introductionmentioning
confidence: 99%
“…These eleven papers were devoted to achieving high-efficiency photocatalysts by broadening the light absorption range, inhibiting the photo-induced electrons and holes recombination, and promoting the extraction of photo-induced charges for chemical reactions. The strategies include defect engineering [1], element doping [2,3], morphology manipulation [3,4], and binary and ternary composite fabrication [5][6][7][8][9][10][11]. Herein, we will provide a brief introduction to these works.…”
mentioning
confidence: 99%
“…Hence, the Cu 2 O-TiO 2 exhibits a hydrogen evolution rate tenfold higher in comparison with bare TiO 2 . Wang et al [7] reported a plasma Ag-modified α-Fe 2 O 3 /g-C 3 N 4 S-Scheme heterojunction that performed much more efficiently than the original g-C 3 N 4 in terms of photocatalytic degradation of tetracycline and hydrogen production. The introduction of Ag nanoparticles expands the light absorption and induces high-energy electrons and photothermal effects from the local surface plasmon resonance effect, which leads to improved photocatalytic activity with joint contributions from the 2D/2D S-Scheme induced electron-hole separation.…”
mentioning
confidence: 99%